1999
DOI: 10.1086/315153
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Viremia in Patients with the Hantavirus Pulmonary Syndrome

Abstract: Hantavirus pulmonary syndrome (HPS) is a rare but acute fulminant disease caused by Sin Nombre virus (SNV). To understand the role of the viral load in the pathogenesis of HPS, the load of virus in the blood of patients with HPS was measured. A quantitative reverse transcription-polymerase chain reaction assay was developed for SNV, because SNV is difficult to grow in cell culture. Thirty-eight samples from 26 patients with HPS were analyzed. Twenty of the 26 initial samples were positive for viral RNA (7 of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 13 publications
8
64
1
6
Order By: Relevance
“…During HPS and DHF, very high levels of viremia are seen, and higher peak viral titers correlate with increased disease severity in both diseases (30,37). We speculate that virusspecific T cells are likely to contribute to the capillary leak syndromes observed in HPS and DHF (20,38,39).…”
Section: Virus-specific Cd8mentioning
confidence: 85%
See 1 more Smart Citation
“…During HPS and DHF, very high levels of viremia are seen, and higher peak viral titers correlate with increased disease severity in both diseases (30,37). We speculate that virusspecific T cells are likely to contribute to the capillary leak syndromes observed in HPS and DHF (20,38,39).…”
Section: Virus-specific Cd8mentioning
confidence: 85%
“…Higher levels of viremia have been found in patients with severe HPS (30). Certain HLA alleles may be associated with highly efficient SNV Ag presentation, as has been speculated in HIV progression (41).…”
Section: Virus-specific Cd8mentioning
confidence: 93%
“…The fact that each hantavirus is associated with a singular primary host suggests that differences in virally regulated host proteins could limit the success of hantaviruses to selected mammals (6). In contrast to animals, transmission of hantaviruses to humans results in two diseases as well as viral clearance from patients and the failure of viruses to establish persistence (33,65,67). This suggests that tactics for cell regulation which are successful in small mammals fail in humans and instead may contribute to pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In HCPS, immunohistochemical studies of lung tissue showed the extensive distribution of viral antigens in endothelial cells, without evidence of cell necrosis. The viral antigens are also present at other sites, such as heart and lymphoid tissue (29). In the lungs, there is considerable infiltration of CD8 lymphocytes, which are also present in peripheral blood in the form of atypical lymphocytes.…”
Section: Pathogenymentioning
confidence: 99%
“…This test usually identifies the viral RNA within seven to ten days of disease onset. Sometimes there are significant differences among viruses isolated from different regions or countries, thus decreasing the technique sensitivity and hindering its use (15,22,29).…”
Section: Diagnosismentioning
confidence: 99%